Molecular Characterization of BsCu/Zn-Superoxide Dismutases and BsMn-Superoxide Dismutases from Chinese Black Sleeper (Bostrychus sinensis) - Haolin Li; Suzhen Ran; Xiaoyu Wang; Bin Shen; Jianshe Zhang (Animals)
Superoxide dismutases (SODs) are critical antioxidant enzymes that protect organisms by catalyzing the dismutation of superoxide radicals into molecular oxygen (O2) and hydrogen peroxide (H2O2). In this study, we cloned the full-length cDNA of two SODs (BsCu/Zn-SOD and BsMn-SOD) from the Chinese black sleeper. The cDNA of BsCu/Zn-SOD consists of 465 nucleotides encoding 154 amino acids, while the BsMn-SOD comprises 678 nucleotides encoding 225 amino acids. The PCR results indicated that in normal tissues, the highest expression of BsCu/Zn-SOD (1.02-fold) was primarily observed in muscle, whereas the highest expression of BsMn-SOD (6.42-fold) was noted in skin. Following treatment with Vibrio parahaemolyticus, the highest expression of BsCu/Zn-SOD (3.67-fold) was detected in the spleen, while BsMn-SOD (3.36-fold) presented the highest expression in the blood. After poly(I:C) treatment, the highest expression of BsCu/Zn-SOD (2.92-fold) was found in the blood, with BsMn-SOD (2.37-fold) showing the highest expression in the spleen. Following Cd2+ treatment, the highest expression of BsCu/Zn-SOD (3.36-fold) was recorded in the liver at the 1/2 96 h LC50 concentration, and in the spleen at both the 1/4 96 h LC50 (2.50-fold) and 1/8 96 h LC50 concentrations. In contrast, BsMn-SOD presented the highest expression (2.60-fold) in the liver across all three concentrations. These findings suggest that both BsCu/Zn-SOD and BsMn-SOD play vital roles in the innate immune response to environmental challenges, laying the foundation for further exploration of antioxidant mechanisms.